Empirical tax research in accounting: A discussion - Maydew, Edward L. (Journal of Accounting and Economics, 2001)
This discussion reflects on the state and future of empirical tax research in accounting, complementing and extending the work of Shackelford and Shevlin ( J. Acc. Econom. 31/32 (2001)). Specifically, this discussion (1) examines the scope of Shackelford and Shevlin (J. Acc. Econom. 31/32 (2001)), (2) discusses what I view to be the main contributions and limitations in the extant tax research, and (3) charts several directions for future research.